New product development team improvisation and speed-to-market: An extended model - Akgün, Ali Ekber; Lynn, Gary S. (My University, 2002)
Speed-to-market is cited as being vital in today's competitive, uncertain and turbulent environments. To help companies in their quest for speed in new product development, many tools and techniques have been developed. One of the these techniques – team improvisation – is receiving a great deal of attention in both practice as well as theory. However, we know surprisingly little about improvisation in a new product development context. In this paper, we extend previous team improvisation models and test them in a new product development context. By studying 354 new product projects, we found that team improvisation has a positive impact on speed-to-market under turbulent markets and technology conditions, and there are some mechanisms that can facilitate a team's ability to improvise, such as team stability and teamwork. We also found that having a clear project goal will detract from a team's ability to improvise. © 2002, MCB UP Limited © 2016 Elsevier B.V., All rights reserved.
Keywords: New product development; Teams; Time-to-market